Environmental assessment of water quality of the Mati River (Albania) based on the use of physico-chemical parameters and aquatic insects as bioindicators - Paparisto, Anila; Lazo, Pranvera; Duka, Sonila; Laknori, Odeta; Valija, Loreta; Pepa, Bledar; Hamzaraj, Etleva; Fierza, Anila (Macedonian Journal of Ecology and Environment, 2012)
The aim of this study was the assessment of the water quality of the Mati River based on the use of selected physico-chemical water quality parameters and benthic insects as bio-indicators. Four stations positioned along the Mati River (Burrel, Shkopet, Rubik, Milot) are selected in the frame of this study. In this paper, are reported 2896 individuals, from 3 phyla (Arthropoda, Mollusca and Annelida) and 5 classes (Insecta, Malacostraca, Gasteropoda, Bivalvia and Clitellata). The most represented class is Insecta with 30 families. The insect orders with the biggest number of the families are Ephemeroptera, Plecoptera, Trichoptera and Diptera, followed by orders Coleoptera and Odonata. EPT (Ephemeroptera, Plecoptera and Trichoptera) - Biotic Index and Biotic Index parameter (Stroud Water Research Center) are used for water quality bio-classification. Water quality parameters (pH, electrical conductivity, dissolved matter, dissolved oxygen, total suspended solids and nutrients) have been measured in those 4 different stations along the Mati River. The waters quality assessment is based on: NIVA classification (Heinonen et.al., 1997) and the European Community Directive (EEC/EEAC/EC 78/659) on “Quality of fresh waters supporting fish life”. The conclusions from the chemical analyses are in good accordance to those obtained from biological parameters.